Graphene Oxide-Carbon Nanotube (GO-CNT) Hybrid Mixed Matrix Membrane for Pervaporative Dehydration of Ethanol - Oindrila Gupta; Sagar Roy; Lingfen Rao; Somenath Mitra (Membranes, 2022)
The pervaporation process is an energy-conservative and environmentally sustainable way for dehydration studies. It efficiently separates close boiling point and azeotrope mixtures unlike the distillation process. The separation of ethanol and water is challenging as ethanol and water form an azeotrope at 95.6 wt.% of ethanol. In the last few decades, various polymers have been used as candidates in membrane preparation for pervaporation (PV) application, which are currently used in the preparation of mixed matrix membranes (MMMs) for ethanol recovery and ethanol dehydration but have not been able to achieve an enhanced performance both in terms of flux and selectivity. Composite membranes comprising of poly (vinyl alcohol) (PVA) incorporated with carboxylated carbon nanotubes (CNT-COOH), graphene oxide (GO) and GO-CNT-COOH mixtures were fabricated for the dehydration of ethanol by pervaporation (PV). The membranes were characterized with Scanning Electron Microscopy (SEM), Fourier Transform Infrared Spectroscopy (FTIR), Thermogravimetric Analysis (TGA), Differential Scanning Calorimetry (DSC), Raman spectroscopy, Raman imaging, contact angle measurement, and water sorption to determine the effects of various nanocarbons on the intermolecular interactions, surface hydrophilicity, and degrees of swelling. The effects of feed water concentration and temperature on the dehydration performance were investigated. The incorporation of nanocarbons led to an increase in the permeation flux and separation factor. At a feed water concentration of 10 wt.%, a permeation flux of 0.87 kg/m2.h and a separation factor of 523 were achieved at 23 °C using a PVA-GO-CNT-COOH hybrid membrane.